Controlled Micro/Nanodome Formation in Proton‐Irradiated Bulk Transition‐Metal Dichalcogenides. Issue 44 (23rd September 2019) - Tedeschi, Davide; Blundo, Elena; Felici, Marco; Pettinari, Giorgio; Liu, Boqing; Yildrim, Tanju; Petroni, Elisa; Zhang, Chris; Zhu, Yi; Sennato, Simona; Lu, Yuerui; Polimeni, Antonio
Abstract: At the few‐atom‐thick limit, transition‐metal dichalcogenides (TMDs) exhibit strongly interconnected structural and optoelectronic properties. The possibility to tailor the latter by controlling the former is expected to have a great impact on applied and fundamental research. As shown here, proton irradiation deeply affects the surface morphology of bulk TMD crystals. Protons penetrate the top layer, resulting in the production and progressive accumulation of molecular hydrogen in the first interlayer region. This leads to the blistering of one‐monolayer thick domes, which stud the crystal surface and locally turn the dark bulk material into an efficient light emitter. The domes are stable (>2‐year lifetime) and robust, and host strong, complex strain fields. Lithographic techniques provide a means to engineer the formation process so that the domes can be produced with well‐ordered positions and sizes tunable from the nanometer to the micrometer scale, with important prospects for so far unattainable applications. Abstract : Proton irradiation of bulk transition‐metal dichalcogenides leads to the blistering of atomically thin domes filled with hydrogen. The domes stud the crystal surface and locally turn the dark bulk material into an efficient light emitter. They can be produced with ordered positions and sizes tunable from the nanometer to the micrometer scale, with important prospects for so far unattainable applications.